Edukasi Kesehatan Reproduksi Dengan Menggunakan Media EMIVO - Putri Al Zahra; Muhammad Imadudin Akbar; Beatrix Elizabeth (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Adolescents today often make mistakes that can lead to deviant sexual behavior due to lack of knowledge about reproductive health. This study aims to determine the effect of reproductive health education with EMIVO (Video Media Education) on the level of reproductive health knowledge of adolescents aged 10-12 years at SDN Karang Sentosa 02. This study used quantitative methods with a Pre-Experimental Pretest-Post Test Only One Group Design research design using purposive sampling technique, with a population of 158 students and a sample of 61 students. Based on the results of the data obtained by researchers, it shows that of the 61 respondents, the most 26 people (42.6%), aged 12 years with female gender as many as 35 people (57.4%), a total of 61 respondents, 41 people (67.2%) of students at SDN Karang Sentosa 02 had good knowledge before being given reproductive health education through EMIVO (Education Media Video) and, as many as 61 people (100%) had good knowledge after being given reproductive health education through EMIVO (Education Media Video). The results showed that reproductive health education with video has a positive effect on adolescent reproductive health knowledge at SDN Karang Sentosa 02. With a 95% confidence level p value of 0.014 <0.05.